Evaluation of Prevalence and Quality of Root Resorption of Second Molar Adjacent the Impacted Third Molar in Cone-Beam Computed Tomograph - Zeynab Arefifard; Maryam Zare Jahromi; Roshnak Ghaffari; Sanaz Mir Sattari (مجله دانشکده دندانپزشکی اصفهان, 2022)
Impacted third molar reduces the bone level in the distal aspect of second molar, and sometimes it can lead to external root resorption of the adjacent second molar. The aim of this study was to evaluate the prevalence and quality of this resorption using cone-beam computed tomography scanning.Materials & Methods:In this descriptive study, CBCT images selected from 60 patients (including 107 maxillary & mandibular impacted third molars) were obtained from patients referring tomaxillofacial radiology department of dental faculty of Islamic Azad University of Isfahan (Khorasgan) in 2016. Under observation of oral radiologist, the images were examined (two times with one-week interval) in axial, coronal, and sagittal sections and recorded to diagnose external root resorption in CBCT. The data were analyzed via descriptive statistics including contingency tables and relative abundance.Results:The prevalence of external root resorption of second molar, adjacent to the third molar were43.25%. The most common type of third molar impaction were mesioangular third molars (41.1%) and in the next level were the vertical (28.1%), and distoangular (18.7) and then horizontal (12.1). The most common location of resorption in mandibular second molar teeth was in 1/3 of cervical (62.5%), and then 1/3 of apical (20.8%) and 1/3 of the middle (12.5%). Also one of teeth resorptions (4.2%) was between the 1/3 of apical and 1/3 of the middle. The most common site of resorption in maxillary second molar teeth was at 1/3 of the apical (68.45%), and then at the 1/3 of the middle (17.35%) and 1/3 of cervical (8.7%). With regards to the severity of resorption; 78.96% of resorptions were mild, 12.03% severe, and 9.03 were moderate.Conclusion:The prevalence of this type of resorption is almost high and the most common position of impacted third molars that resulted in this type of resorption are mesioangular and horizontal. Most common site of resorption in the maxilla was 1.3 of the apical and in the mandible was 1.3 of the cervical, which were often mild in resorption.